Salivary Matrix Metalloproteinase-8 (MMP-8) in Relation to Periodontal Health Status Among a Group of Hypertensive Patients - Iman Z AlMudaris; Nadia A AlRawi (College of Dentistry/ University of Baghdad, 2018)
Background: Hypertension is probably the most important public health problem around the world. People with periodontal disease may be at greater risk of hypertension. The inflammatory effects of periodontal disease help to promote endothelial dysfunction in arteries which may lead to changes in blood pressure. Salivary MMP-8 has been associated with both periodontal disease and prevalent hypertension. Aim of study: This study was conducted to measure salivary matrix metalloproteinase - 8, in relation to periodontal health condition among a group of patients with hypertension in comparison with control group. Materials and methods: Ninety subjects, aged 45-50 years old were included in this study, seeking treatment for chest pain in Ibn-AlBaytar center for cardiac surgical treatments in Baghdad, Iraq. The subjects were divided into study group (45 patient) who were diagnosed to be a hypertensive patient, and a control group (45 subject), with no hypertension. Plaque status was evaluated according to the Silness and Loe, probing pocket depth and clinical attachment level. Unstimulated saliva was collected from all subjects to analyses MMP-8. Result: A high mean value of plaque index, clinical attachment level and probing pocket depth for the study group than the control group with statistically no significant difference. In addition to that, a significant positive correlation between the plaque index and the clinical attachment level among both groups. Salivary MMP-8 level showed a higher level in the study group than in the control group, with statistically significant difference between groups, and a significant positive correlation was detected between salivary MMP-8 with plaque index, among study group, Conclusions: Higher percentage of periodontal diseases was found among patients with blood hypertension. In addition, high level of salivary MMP-8 is potentially associated with periodontal status of the study group.